2018
DOI: 10.1177/1403494818773530
|View full text |Cite
|
Sign up to set email alerts
|

Mental health interventions among older adults: A systematic review

Abstract: No specific interventions could be recommended on the aforementioned basis. We conclude that a number of factors are of central importance for an intervention to have the desired effect. If these factors are considered, mental health can be successfully promoted among older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 43 publications
(93 reference statements)
0
17
0
Order By: Relevance
“…Maintaining the psychological health of older adults is of high importance ( 109 ). Besides the loss of physical abilities and structures, the aging process and supplemental (chronic) diseases have a significant influence on individuals' psychological health ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Maintaining the psychological health of older adults is of high importance ( 109 ). Besides the loss of physical abilities and structures, the aging process and supplemental (chronic) diseases have a significant influence on individuals' psychological health ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous qualitative research has highlighted that entering into discussions about social needs and QoL with a staff member facilitates better matching of client needs to appropriate services [ 21 ]. Other evidence also suggests that older adults with lower QoL may benefit more from programs that involve iterative feedback from a healthcare professional and are tailored to their specific social, cognitive and physical needs [ 58 ]. However, discussions about QoL can be emotionally difficult for staff [ 21 ] and more resource intensive than traditional clinical process indicators.…”
Section: Discussionmentioning
confidence: 99%
“…Only two studies focussed on mental wellbeing and social participation, one showed some effects in reducing loneliness [45] and the other in improving general mental health [16]. This gap in research has also been supported in other reviews, where promoting wellbeing and mental health have shown to be both effective and potentially cost-effective [122,123], and should, therefore, be further researched.…”
Section: Discussionmentioning
confidence: 98%